Experimental exploration of five-qubit quantum error-correcting code with superconducting qubits. Issue 1 (21st January 2021) - Gong, Ming; Yuan, Xiao; Wang, Shiyu; Wu, Yulin; Zhao, Youwei; Zha, Chen; Li, Shaowei; Zhang, Zhen; Zhao, Qi; Liu, Yunchao; Liang, Futian; Lin, Jin; et al.
Abstract: Quantum error correction is an essential ingredient for universal quantum computing. Despite tremendous experimental efforts in the study of quantum error correction, to date, there has been no demonstration in the realisation of universal quantum error-correcting code, with the subsequent verification of all key features including the identification of an arbitrary physical error, the capability for transversal manipulation of the logical state and state decoding. To address this challenge, we experimentally realise the [5, 1, 3] code, the so-called smallest perfect code that permits corrections of generic single-qubit errors. In the experiment, having optimised the encoding circuit, we employ an array of superconducting qubits to realise the [5, 1, 3] code for several typical logical states including the magic state, an indispensable resource for realising non-Clifford gates. The encoded states are prepared with an average fidelity of $57.1(3)%$ while with a high fidelity of $98.6(1)%$ in the code space. Then, the arbitrary single-qubit errors introduced manually are identified by measuring the stabilisers. We further implement logical Pauli operations with a fidelity of $97.2(2)%$ within the code space. Finally, we realise the decoding circuit and recover the input state with an overall fidelity of $74.5(6)%$, in total with 92 gates. Our work demonstrates each key aspect of the [5, 1, 3] code and verifies the viability of experimental realisation of quantum error-correcting codes with superconducting qubits. Abstract : Experimental demonstration of encoding, decoding, logical operation, and error detection of a five-qubit error correcting code on a superconducting quantum processor.